STRATEGI KOMISI PEMILIHAN UMUM (KPU) DALAM PENINGKATAN PERAN PEREMPUAN PADA PEMILIHAN KEPALA DAERAH DAN WAKIL KEPALA DAERAH PESAWARAN TAHUN 2020 - Eka Suaib; Yetti Reffiani (e-JKPP, 2020)
The national target has not been achieved in the previous pilkada, which is a phenomenon in general elections. The formulations of the problems in this study are: (1) What is the KPU's Strategy in Increasing the Role of Women in the 2020 Pilkada Pesawaran? and (2) What factors hinder the increase in the role of women in the 2020 Pilkada?The research method of qualitative descriptive data analysis includes data collection, data reduction is collected from research into notes that have been checked, data presentation is to arrange information in a certain way so that it requires drawing conclusions or taking action.The research objective is to provide an understanding, description of the General Election Commission's strategy in enhancing the role of women in the 2020 election for the Regent and Deputy Regent of Pesawaran, using the analysis of Strengths, Weaknesses, Opportunities, Threats (SWOT).The results showed: Maximizing the ability of electronic media and internet media to socialize, Increasing cooperation from related organizations to socialize, and Validating Voter Data and as inhibiting factors, namely: Human Resources, Owned Budget, Not maximal use of social media, facilities and limited infrastructure, limited space for movement.